2021
DOI: 10.1097/cu9.0000000000000002
|View full text |Cite|
|
Sign up to set email alerts
|

Transgender surgery – Knowledge gap among physicians impacting patient care

Abstract: Transgender surgeries are increasingly performed across the globe and in the United States. Although comprehensive centers exist, which are well equipped to cater and tailor to the needs of this population subset, quite often their resultant complications are handled at a different institution owing to the acuity of the condition. However, interestingly the psychosocial needs, medical pathophysiology, available surgical procedures, and their resultant complications are still not a part of the regular medical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Currently, very few transgender surgeries are performed on youth in the United States. Literature focused on adult patients does note a variable rate of complication, dependent on the procedure performed [21]. As with all pediatric patients, TGD youth should be well informed about details of the surgery and possible complications, undergo behavioral health evaluation, and consult all members of their care team, prior to making the decision to undergo a life changing and possibly irreversible procedure [11 && ].…”
Section: External/surgical Considerationsmentioning
confidence: 99%
“…Currently, very few transgender surgeries are performed on youth in the United States. Literature focused on adult patients does note a variable rate of complication, dependent on the procedure performed [21]. As with all pediatric patients, TGD youth should be well informed about details of the surgery and possible complications, undergo behavioral health evaluation, and consult all members of their care team, prior to making the decision to undergo a life changing and possibly irreversible procedure [11 && ].…”
Section: External/surgical Considerationsmentioning
confidence: 99%
“…Retrospective review of a cohort of 55 GGAS patients with urinary complications revealed that within a median of four months of surgery, nearly 75% of patients presented with two or more complications: 86% strictures and 56% fistulae (46). Many patients travel long distances for their initial GGAS (47), therefore this is relevant for urologists across the country (48).…”
Section: Incidence Of Urinary Symptoms After Ggasmentioning
confidence: 99%
“…Transgender individuals, those whose gender identity differs from the sex assigned at birth, often pursue gender-affirming medical interventions, including hormone therapy and various surgical procedures [ 1 ]. These interventions can lead to complex anatomical considerations, such as the presence of neovagina and, as highlighted in this case, the presence of a prostate.…”
Section: Introductionmentioning
confidence: 99%